2021
DOI: 10.31138/mjr.32.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Related Liver Cirrhosis in Psoriatic Arthritis: A Case Report and Review of the Literature

Abstract: Methotrexate is an anchor-drug for the treatment of inflammatory arthritides affecting peripheral joints, such as rheumatoid and psoriatic arthritis (PsA), but also for other immune-mediated diseases like psoriasis. Although it is generally a well-tolerated drug, adverse effects often occur. Reversible derangement of liver function test is the most common laboratory adverse event. However, in some cases, liver cirrhosis and/or fibrosis can occur. Besides, many of these diseases like PsA and psoriasis are close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Its long-term use has been related to severe liver toxicity, hepatic fibrosis, and eventually liver cirrhosis, although those findings only included old studies based on individuals who received a high dose administered daily. Newer studies have shown that MTX rarely induces liver fibrosis per se, but rather it acts synergistically with other hepatotoxic factors, such as diabetes mellitus or metabolic syndromes including obesity, increased body mass index, and dyslipidemia, which are strongly associated with PsA, or alcohol consumption [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its long-term use has been related to severe liver toxicity, hepatic fibrosis, and eventually liver cirrhosis, although those findings only included old studies based on individuals who received a high dose administered daily. Newer studies have shown that MTX rarely induces liver fibrosis per se, but rather it acts synergistically with other hepatotoxic factors, such as diabetes mellitus or metabolic syndromes including obesity, increased body mass index, and dyslipidemia, which are strongly associated with PsA, or alcohol consumption [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…Newer techniques such as MRE may help with the further follow-up of patients undergoing biological and non-biological treatments to evaluate treatment hepatotoxicity, as it showed a higher success rate and diagnostic accuracy than Fibroscan, with comparable results to liver biomarkers [ 122 , 123 , 124 ]. Further studies on a larger population are necessary to validate the actual data.…”
Section: Discussionmentioning
confidence: 99%